PERANCANGAN MEDIA PEMBELAJARAN PENGENALAN BENDERA PADA ANAK KELAS 1 SDIT EL FATAH BERBASIS CONSTRUCT 2 - Hamdan; Ofan Sofian; Ummy Kalsum; Rudianto; Neng Yuli Yana (Universitas Majalengka, 2024)
This study aims to design and develop a learning application focused on introducing flags to first-grade students at SDIT EL Fatah. The application is designed using the Construct 2 platform, a tool that allows the development of interactive applications without requiring deep programming skills. This application integrates various interactive features that include learning materials, quizzes, user profiles, and usage instructions. The learning materials are presented in engaging and easy-to-understand slides, while the quizzes are designed to test and reinforce students' understanding of the material they have learned. The user profile feature allows students to track their learning progress, and the usage instructions provide clear guidance for navigating the application.The research method used is Research and Development (R&D), which includes steps such as identifying potential and problems, data collection, product design, design validation, design revision, product testing, product revision, and mass production. The results of this study indicate that this flag introduction learning application is effective in increasing students' interest and understanding of historical material. The application also received positive responses from teachers and students, indicating that the use of technology in learning can enhance student interaction and engagement.Therefore, this application is expected to become an innovative and effective learning solution, particularly in the context of primary education in Indonesia. This study also contributes to the development of technology-based learning methods that can be applied to various other subjects in primary schools